2022
DOI: 10.3390/pharmaceutics14051087
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro CRISPR/Cas9 Transfection and Gene-Editing Mediated by Multivalent Cationic Liposome–DNA Complexes

Abstract: Clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated nuclease 9 (Cas9) gene-editing offers exciting new therapeutic possibilities for disease treatment with a genetic etiology such as cancer, cardiovascular, neuronal, and immune disorders. However, its clinical translation is being hampered by the lack of safe, versatile, and effective nonviral delivery systems. Herein we report on the preparation and application of two cationic liposome–DNA systems (i.e., lipoplexes) for CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 70 publications
1
8
0
Order By: Relevance
“…When permanent cationic lipid-DOTAP is applied, the poor transfection efficiency of dLNP is likely attributed to the inefficient intracellular release of encapsulated siRNA into the cytoplasm. This finding is in agreement with another study reporting the poor transfection efficiency of DOTAP-containing lipoplexes, which corroborated to inefficient DNA release from DOTAP cationic vesicles into the cytoplasm [ 43 ]. Yung et al reported a combination formulation with amine and tertiary amine cationic lipids, which achieved superior delivery of microRNA-21 [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…When permanent cationic lipid-DOTAP is applied, the poor transfection efficiency of dLNP is likely attributed to the inefficient intracellular release of encapsulated siRNA into the cytoplasm. This finding is in agreement with another study reporting the poor transfection efficiency of DOTAP-containing lipoplexes, which corroborated to inefficient DNA release from DOTAP cationic vesicles into the cytoplasm [ 43 ]. Yung et al reported a combination formulation with amine and tertiary amine cationic lipids, which achieved superior delivery of microRNA-21 [ 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…These vesicles excel in transmitting genetic material into target cells, facilitating the delivery of nucleic acids such as DNA or RNA [ 98 , 102 ]. The efficiency of this process, known as transfection, is vital in manipulating cellular functions and studying gene expression [ 104 ]. Liposomes, with their ability to encapsulate and protect genetic material, enhance transfection efficiency by ensuring the successful integration of foreign genetic material into the host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Despite early challenges of low transfection efficiency, liposome formulations have been developed to deliver siRNA, plasmid DNA, and mRNA for gene silencing, replacement, and protein expression [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Surface modifications of liposomes with ligands, such as antibodies or peptides, have been a focus of research, enabling selective binding to specific receptors on target cells and improving delivery efficiency [ 12 , 13 , 35 , 36 , 37 , 38 ]. Additionally, stimuli-responsive liposomes were engineered to release their cargo in response to environmental cues, such as pH changes or ultrasound activity [ 37 , 39 , 40 , 41 ].…”
Section: Liposome-based Delivery Systemmentioning
confidence: 99%
“…Liposomes have been extensively engineered to optimize the delivery of CRISPR/Cas and gRNA [ 12 , 13 , 35 , 36 , 37 , 40 , 50 , 51 , 52 ]. The combination of the CRISPR-based system with liposome delivery technology enables precise and efficient genetic modifications in cells and tissues.…”
Section: Liposome-based Crispr Deliverymentioning
confidence: 99%
See 1 more Smart Citation